2009
DOI: 10.1021/jp908874k
|View full text |Cite
|
Sign up to set email alerts
|

Heterojunction of FeTiO3 Nanodisc and TiO2 Nanoparticle for a Novel Visible Light Photocatalyst

Abstract: For the first time, a single crystalline FeTiO 3 nanodisc in the ilmenite phase has been synthesized by a hydrothermal reaction at 220 °C. The prepared FeTiO 3 was a hexagonal disk-like structure with an average diameter of ∼400 nm and a thickness of ∼70 nm, while its hexagonal face was oriented in (001) plane and grown to (110) direction. The heterojunction structure was formed between the as-prepared FeTiO 3 nanodisc and Degussa P25 with an average particle size of ∼25 nm by employing maleic acid as an organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(86 citation statements)
references
References 38 publications
2
79
0
Order By: Relevance
“…To provide intimate contact between the In 2 O 3 and TiO 2 nanoparticles, maleic acid was utilized as an organic linker. The role of added maleic acid is to chemically combine In 2 O 3 and TiO 2 nanoparticles through its dicarboxylic functional groups [14], as shown in Scheme 1. To avoid the possible errors in measuring the photocatalytic efficiency of the composite In 2 O 3 /TiO 2 due to the presence of maleic acid, the heterojunction structure In 2 O 3 /TiO 2 was kept under UV light for 72 h and thus, maleic acid will be completely degraded by the photocatalytic reaction with the heterocomposite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide intimate contact between the In 2 O 3 and TiO 2 nanoparticles, maleic acid was utilized as an organic linker. The role of added maleic acid is to chemically combine In 2 O 3 and TiO 2 nanoparticles through its dicarboxylic functional groups [14], as shown in Scheme 1. To avoid the possible errors in measuring the photocatalytic efficiency of the composite In 2 O 3 /TiO 2 due to the presence of maleic acid, the heterojunction structure In 2 O 3 /TiO 2 was kept under UV light for 72 h and thus, maleic acid will be completely degraded by the photocatalytic reaction with the heterocomposite.…”
Section: Resultsmentioning
confidence: 99%
“…The design of the heterocomposite structure between a narrow band gap semiconductor which is called sensitizer and TiO 2 with matching energy band potentials provides an effective way to extend the photosensitivity of TiO 2 into the visible region [14][15][16][17][18][19][20][21]. Thus far, variety of coupled semiconductor systems, including AgI/BiOI, Ag/AgBr/WO 3 .H 2 O, CdS/TiO 2 , CdSe/TiO 2 , Bi 2 O 3 /SrTiO 3 , WO 3 /WS 2 , CdS/AgI [22][23][24][25][26][27][28] and others were reported to be an efficient photocatalyst for the decomposition of organic pollutants under visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the BiOCl/Bi3O4Cl system could be a Type-B heterojunction photocatalyst. 15,[24][25][26] With irradiation of visible light, the electrons in VB of Bi3O4Cl are excited to its CB. Thereby VB of Bi3O4Cl is rendered partially vacant, and the electrons in VB of BiOCl can be transferred to that of Bi3O4Cl.…”
Section: Resultsmentioning
confidence: 99%
“…In the first synthesis method, the reactants must be heated up to 1200°C under oxygen atmosphere to prepare an iron titanate [3,7,8] that is not completely homogeneous. Hydrothermal synthesis requires use of unstable alkoxides under special reaction conditions that are difficult to maintain [9,10]. FeTiO 3 can also be prepared by grinding TiO 2 in a high-speed steel ball mill under oxygen atmosphere [11].…”
Section: Introductionmentioning
confidence: 99%
“…They also reported that commercial ilmenite mixed with TiO 2 and illuminated with visible light exhibits photocatalytic activity for degradation of 4-chlorophenol in liquid phase and 2-propanol in gas phase. Kim et al [10] also reported that a heterojunction catalyst of FeTiO 3 prepared by the hydrothermal method and TiO 2 (Degussa P25) showed good photocatalytic activity for mineralization of 2-propanol in gas phase under visiblelight irradiation (k C 420 nm). Nanosized FeTiO 3 /TiO 2 catalysts synthesized by a hydrothermal method exhibited good photocatalytic activity for transformation of CO 2 to methanol under both visible and UV light irradiation [19].…”
Section: Introductionmentioning
confidence: 99%